BOARD GAME AS AN EDUCATIONAL GAME MEDIA TO EFFORT THE ATTITUDE CHANGE OF DENGUE PREVENTION IN SCHOOL-AGED CHILDREN: DOI: https://doi.org/10.35654/ijnhs.v1i2.12 - Vivi Leona Amelia; Agus Setiawan; Sukihananto Sukihananto (Alta Dharma Publisher, 2018)
Background: Indonesia is the second highest country for dengue prevalence, and the cases has rapidly increased in the last 45 years. Compared to other age groups, the age group of children is the highest dengue fever prevalence. The attitude of dengue prevention is important for child which related to their skill to preventing the dengue fever by themselves. A game is one of the way to teach the children for a new information, it is also including the dengue prevention material Objective: This study want to identify the attitude of the children about dengue prevention and develop an educational game to teach a new information about dengue prevention. Methods: This study uses quasi-experimental design with pre and posttest with control group. The participants are a school-aged children with age 10-12 years old. With total 92 participants, and 46 for each group. Results: The results show a significantly increasing score at children attitude of dengue prevention before and after intervention except the strategy to closing the water storage (p=0.008), the other strategy that gets a significantly increasing such as fever and fever management (p=0.000), draining the water storage (p=0.001), checking the water storage (p=0.000), recycling (p=0.000), chemistry agent (p=0.000), biology agent (p=0.000), self protection (p=0.001), immune system (0.000). There are different attitude between control and intervention groups (p=0.000). Conclusion: The conclusion is the dengue board game can be an educational game media to give dengue prevention information to children, also can improving the attitude of dengue prevention. Keywords: Board Game, Dengue Prevention Strategy, School-Aged Children